1981
DOI: 10.1080/09553008114550781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heavy Ions on Rabbit Tissues: Loss of Electroretinogram and DNA Repair in Retinal Photoreceptor Cells

Abstract: Optic and proximate tissues of New Zealand white rabbits were exposed to the Bragg plateau regions of 530 MeV/amu Ar ions and 365 MeV/amu Ne ions and also to 60Co gamma rays. The linear energy transfers (LET infinity s) for the radiations were 90 +/- 5, 35 +/- 3 and 0.3 keV/micrometer, respectively. Single acute exposures to all three radiations caused only limited changes in the electroretinogram (ERG) until a critical dose was approached. At that dose, which was 45 +/- 3 Gy for all three types of radiation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 11 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…In the late 1970s, it was shown that DNA strand breaks (total strand breaks including single/double strand breaks) induced by high‐LET heavy ions are rejoined less efficiently than those by X‐rays, leaving higher rate of nonrejoined DNA breaks with high‐LET irradiations. This phenomenon is LET dependent and became maximal at 150–200 keV/μm LET range 68–70. In the early to mid 1990s, rejoining of DNA DSBs by heavy ions were measured first by neutral filter elution and then by pulsed field gel electrophoresis and static field gel electrophoresis (SFGE) 30, 35, 71–75.…”
Section: Repair Of Dsbs Induced By High‐let Heavy Ionsmentioning
confidence: 99%
“…In the late 1970s, it was shown that DNA strand breaks (total strand breaks including single/double strand breaks) induced by high‐LET heavy ions are rejoined less efficiently than those by X‐rays, leaving higher rate of nonrejoined DNA breaks with high‐LET irradiations. This phenomenon is LET dependent and became maximal at 150–200 keV/μm LET range 68–70. In the early to mid 1990s, rejoining of DNA DSBs by heavy ions were measured first by neutral filter elution and then by pulsed field gel electrophoresis and static field gel electrophoresis (SFGE) 30, 35, 71–75.…”
Section: Repair Of Dsbs Induced By High‐let Heavy Ionsmentioning
confidence: 99%
“…Keng and Lett (Keng and Lett 1981) have also studied the effects on retinal photoreceptor cells of a variety of radiation qualities, including 6oCo y-rays, and heavy ions (LET of 90 and 35 keV km-'). Their result showed that a critical dose of 45 f 3 Gy was required to initiate a sudden loss in the b-wave of the ERG, independent of the type of radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments on rabbit retinas cited here have shown conclusively that destruction of proliferating cells are not involved in the loss of ERG, since this loss is independent of radiation quality. Furthermore, the abrupt threshold of dose required to produce the critical damage suggests that the disruption of a membrane and/or interference with a biochemical process is involved (Keng and Lett 1981). The interpretation is thus made that damage to the photoreceptor cells is responsible for the loss in ERG (Noell 1980).…”
Section: Discussionmentioning
confidence: 99%